The need for pertussis vaccination among older adults and high-risk groups: a perspective from advanced economies of the Asia Pacific region. (2nd December 2021) - Hoe Nam, Leong; Chiu, Cheng-Hsun; Heo, Jung Yeon; Ip, Margaret; Jung, Ki-Suck; Menzies, Robert; Pearce, Rodney; Buchy, Philippe; Chen, Jing; Nissen, Michael; Oh, Kyu-Bin
ABSTRACT: Introduction : Influenza and pneumococcal vaccines are the most regularly prescribed vaccines amongst adults <65 years of age. Pertussis booster vaccines (available as combined diphtheria-tetanus-acellular pertussis, Tdap) uptake is relatively low in many countries in the Asia-Pacific region. Increasing Tdap vaccination is a strategy that may aid healthy aging. Areas Covered : Epidemiology data, including notification reports from 6 advanced economies in Asia (Australia, Hong Kong, New Zealand, Singapore, South Korea, and Taiwan) were reviewed to assess the pertussis disease burden and identify high-risk groups. Existing Tdap vaccination recommendations were reviewed. Current vaccination practices were discussed to benchmark and identify barriers and success factors for Tdap booster vaccination in older adults. Expert Opinion : The available evidence supports Tdap vaccination at an individual level for the prevention of pertussis, along with tetanus and diphtheria in those aged 65+ years, together with influenza and pneumococcal vaccination. Data gaps need to be filled to support the development of national/supranational recommendations for pertussis booster vaccination. Groups at higher risk of pertussis infection and its complications, including those with chronic obstructive pulmonary disease and asthma, could be considered as priority groups. Increasing disease awareness and establishing adult vaccination registries could improve vaccine coverage and promote healthy aging. PLAIN LANGUAGE SUMMARY: Pertussis, also called whooping cough, is a common disease in adults. However, how it affects adults in some countries in the Asia-Pacific region is not well understood. In 2019, a panel of experts met to review the available information on adult cases of pertussis in Australia, Hong Kong, New Zealand, Singapore, South Korea, and Taiwan. Here, we present the outcomes of the meeting. Pertussis is increasingly reported in the Asia-Pacific region, including cases diagnosed in adults. The diagnosis may be missed in countries where awareness is still low and/or it is not tested routinely. The experts concluded that physicians should consider recommending pertussis vaccination to older adults (aged 65 or older) on an individual basis, as well as people with asthma or chronic obstructive pulmonary disease, who appear to be at higher risk of severe pertussis. Uptake of pertussis vaccination in adults could be improved by increasing awareness of the vaccines available and vaccination infrastructure for this age-group. Some of the measures proposed were as follows: improved access to vaccination; personalized reminders when vaccines are due; and more education about pertussis in adults for doctors, nursesnurses, and patients. The experts also proposed setting up adult vaccination registries for tracking and evaluation of vaccine uptake. This expert opinion might help the healthcare community build action plans to recognise the burden of the disease and increase rates of vaccination among adults. In addition, better data on the disease burden would help to generate awareness. Abstract :